Hazardous activities and civil strict liability: The regulator's dilemma - Gérard Mondello (Fondazione Eni Enrico Mattei (FEEM), 2011)
This paper addresses the conditions for setting up strict civil liability schemes. For that it compares the social efficiency of two main civil liability regimes usually enforced to protect the environment: the strict liability regime and the capped strict liability scheme. First, it shows that the regulator faces an effective dilemma when he has to enforce one of these schemes. This because the social cost of a severe harm (and the associated optimum care effort) is determined independently of any liability regime. This independency has economic consequences. First, victims and polluters pit one against another about the liability regime that the government should enforce. Hence, financially constrained polluters prefer the ceiling of responsibilities while victims wish to extend the amount of redress under a standard strict liability. Economic criteria for enforcing a regime rather than another one are lacking. Second, the paper shows that implementing civil strict liability rules may be done by setting up care standards as for instance in the nuclear or the maritime sectors and demanding to the injurers to comply with them. We show that this goal can be achieved by resorting to some friendly monitoring corresponding to frequent random controls with low fines rather than few controls that should involve heavy fines.
Keywords: K0; K32; Q01; Q58; 330; Environment; Strict Liability; Ex-Ante Regulation; Ex-Post Liability; Judgment-Proof; Environment Law; CERCLA; Environmental Liability